Association between forced expiratory volume in 1 s and relapse-free survival in operable non-small cell lung cancer: a prospective cohort study with propensity score overlap weighting - Wu, Shaoping; Fu, Siqian; Ripley-Gonzalez, Jeffrey William; Cui, Ni; Du, Yang; Sylvester, Karl; You, Baiyang; Xu, Ning; Cheng, Jing; Dun, Yaoshan; Liu, Suixin (BMJ open, 2024)
ObjectivesInvestigate the correlation between the percentage of predicted forced expiratory volume in 1 s (FEV1%pred) and survival outcomes, namely relapse-free survival (RFS) and overall survival (OS), in patients diagnosed with operable early-stage non-small cell lung cancer (NSCLC).DesignProspective observational study.SettingClinical settings in Xiangya Hospital, Central South University, Hunan, China.ParticipantsFrom November 2014 to December 2019, 775 operable patients with NSCLC, median age 58 years (IQR 13) with 40.6% women, were consecutively enrolled and underwent preoperative FEV1 assessment. All participants were evaluated using the FEV1%pred assessment. Subsequent treatments and operative interventions followed established protocols for NSCLC.ResultsDuring the follow-up, which lasted a median of 40 months (range 1–85 months) and continued until December 2021, 202 patients either relapsed or died. Optimal FEV1%pred cut-off was identified using receiver operating characteristic analysis. Results revealed 110 and 71 relapses and deaths per 1000 person-years for patients with FEV1 values of <82%pred and ≥82%pred, respectively. Cox proportional hazards models, adjusted for demographics, medical history and surgery characteristics with propensity score overlap weighting, revealed the significant impact of lower FEV1%pred on decreased RFS and OS. An FEV1%pred less than 82% displayed a significant association with decreased RFS (weighted HR, 1.55; 95% CI, 1.14 to 2.09; p=0.007) and OS (weighted HR, 1.50; 95% CI, 1.01 to 2.23; p=0.04).ConclusionsLower FEV1%pred values notably correlate with compromised RFS and OS in individuals operable for early-stage NSCLC, suggesting that FEV1%pred may serve as a valuable tool in evaluating and managing long-term recurrence risk in patients with early-stage NSCLC.Trial registration numberChiCTR2100048120.